DISCRETE CONTROL OF FORM-BUILDING TOOL WEAR RESISTANCE - V.S. MINAKOV; D.A. CHILIKIN; D.N. MALEEV (Advanced Engineering Research)
In the given work with purpose of geometry restoration and hardening of the form-building tools without removing from the machine tool considered the opportunity of protective wear resistance coatings production using discrete ELAC technology (electro-acoustic coating).